2021
DOI: 10.1101/2021.08.25.457676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding of AP endonuclease-1 to G-quadruplex DNA depends on the N-terminal domain, Mg2+and ionic strength

Abstract: The base excision repair enzyme apurinic/apyrimidinic endonuclease-1 (APE1) is also engaged in transcriptional regulation. APE1 can function in both pathways when the protein binds to a promoter G-quadruplex (G4) bearing an abasic site (modeled with tetrahydrofuran, F) that leads to enzymatic stalling on the non-canonical fold to recruit activating transcription factors. Biochemical and biophysical studies to address the binding and catalytic activity of APE1 with the vascular endothelial growth factor (VEGF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…51 Our prior work found the binding between catalytically inactivated APE1 and a G4 was Mg 2+ -dependent. 57 Therefore, the discussion here will focus on the Sm 3+ studies, but for completeness of the study, binding without Mg 2+ was analyzed and is provided in Figure S10. First, an endonuclease assay control study was conducted to show that no cleavage occurs with 10 mM Sm 3+ present (Figure S11).…”
Section: Oxidation Of Ape1 Decreases Endonuclease Activitymentioning
confidence: 90%
See 3 more Smart Citations
“…51 Our prior work found the binding between catalytically inactivated APE1 and a G4 was Mg 2+ -dependent. 57 Therefore, the discussion here will focus on the Sm 3+ studies, but for completeness of the study, binding without Mg 2+ was analyzed and is provided in Figure S10. First, an endonuclease assay control study was conducted to show that no cleavage occurs with 10 mM Sm 3+ present (Figure S11).…”
Section: Oxidation Of Ape1 Decreases Endonuclease Activitymentioning
confidence: 90%
“…To understand the role of cysteine oxidation to sulfenic acids in APE1 in influencing DNA binding, fluorescence anisotropy binding assays were conducted following a method previously reported. 57 The binding studies were conducted using the sequences shown in Table 1.…”
Section: Oxidation Of Ape1 Decreases Endonuclease Activitymentioning
confidence: 99%
See 2 more Smart Citations